Aspiring Narratives of Previous Births in Written and Visual Media from Ancient Gandhāra. Issue 1 (24th June 2019) - Neelis, Jason
Abstract : A wide range of practices emerged for venerating the Buddha's embodied presence in textual and visual relics.This article considers ways in which hagiographical narratives of previous births preserved in written and visual media may be considered as embodiments in Dharma (Dharmakāya). The study focuses on Gāndhārī Buddist manuscipts with abbreviated written summaries of narratives labeled as Avadānas and Pūrvayogas. Results of a survey of images identified as Jātakas in Gandhāran art are also integrated for a comprehensive understanding of the iconic function of rebirth narratives, which were emplaced in the sacralized landscape of the Northwest.